Factors affecting exclusive breastfeeding in term infants - Novitria Dwinanda; Badriul Hegar Syarif; Damayanti Rusli Sjarif (Indonesian Pediatric Society, 2018)
Background Exclusive breastfeeding by healthy mothers to their healthy, term babies who underwent vaginal birth, should be readily accomplished. However, exclusive breastfeeding by Indonesian mothers has declined.Objective To assess the monthly success rate prevalences for exclusive breastfeeding for the first 6 months of life, as well as factors that affect exclusive breastfeeding.Methods A prospective cohort study was conducted in 243 healthy mothers with healthy term babies who underwent normal births at Cipto Mangunkusumo Hospital (CMH), Jakarta, Indonesia. Guided interviews were conducted monthly for six months. Bivariate and multivariate analyses were performed on the factors potentially affecting breastfeeding with equal subject numbers.Results Exclusive breastfeeding prevalences were 64.8% (first month), 53.7% (second month), 43% (third month), 30.7% (fourth month), 23.5% (fifth month), and 22.3% (sixth month). Multivariate analysis revealed that the mother’s confidence in breast milk production, as well as husband or family support, affected the success of exclusive breastfeeding for each month. Maternal not working/studying outside the home affected the success of exclusive breastfeeding in the third (RR 3.38; 95%CI 1.21 to 9.43) and fourth months (RR 6.56; 95%CI 1.39 to 30.99).Conclusion Exclusive breastfeeding prevalences in Cipto Mangunkusumo Hospital decrease in a monthly fashion up to the sixth month. Several factors affecte the success rate for each month in the six month period, including maternal confidence in breast milk production and family support.